Pretreatment Seizure Frequency, Control & Remission - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
The effect of the number of seizures before antiepileptic drug (AED) treatment on the ease of seizure control and remission was studied in a population-based regional cohort of 479 children with epilepsy at the IWK Children's Hospital, Halifax, Nova Scotia, Canada.